2023
DOI: 10.61108/ijsshr.v1i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Outsourcing and Firm Performance: A Review of Literature

Muo Charles,
Sei Benson Ochieng

Abstract: Despite the fact that firms collectively contribute to the socio-economic development of the national economy, most firms nowadays are face difficulties in maintaining superior firm performance; occasioned by unmanageable business environment uncertainty and changes. It is for this reason that the idea of strategic outsourcing has evolved in response to changes in the business environment and uncertainty. Despite vast empirical research on the relationship between strategic outsourcing and firm performance, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…The study found a very strong and positive relationship between reverse logistics and the performance of footwear manufacturing firms in Kenya (r=0.926, p-value=0.000). The p-value=0.000 was less than 0.05, thus the relationship was considered to be significant (Charles, & Benson Ochieng, 2023). These findings are in line with Mbovu and Mburu (2018) arguments that manufacturing firms' competitiveness in Kenyan industrial companies is influenced by reverse logistics practices.…”
Section: Correlation Analysissupporting
confidence: 77%
“…The study found a very strong and positive relationship between reverse logistics and the performance of footwear manufacturing firms in Kenya (r=0.926, p-value=0.000). The p-value=0.000 was less than 0.05, thus the relationship was considered to be significant (Charles, & Benson Ochieng, 2023). These findings are in line with Mbovu and Mburu (2018) arguments that manufacturing firms' competitiveness in Kenyan industrial companies is influenced by reverse logistics practices.…”
Section: Correlation Analysissupporting
confidence: 77%
“…The opponents argue that TBV is anchored on conceptual and empirical methodology. Charles, & Benson (2023). argues that the theory ignores the process issues.…”
Section: Resource Based View Theorymentioning
confidence: 99%
“…The globalization of supply chains and the division of labor refinement have made production outsourcing more and more popular among manufactures. Self-production and outsourcing have become important production strategies for manufactures [1]. As consumers pay more attention to product quality, products with advanced processes tend to win consumers' favor.…”
Section: Introductionmentioning
confidence: 99%
“…H However, due to technical errors, Intel has lagged behind TSMC in recent years by a whole generation of technology updates, and product quality has been questioned. Forced by competition and technological pressure, Intel announced that it will launch its leading CPU products manufactured by TSMC in 2023 1 .…”
Section: Introductionmentioning
confidence: 99%